Teaching Methods based on Futures Studies Development in Iran Higher Education Curriculum - Keshavarzi, Mehdi; Yarmohammadian, Mohammad Hossein; Nadi, Mohammad Ali (Iranian evolutionary educational psychology journal, 2019)
One of the tasks of a university is student's competencies in different areas, including recognition of the future or futures studies. The growth of Students through improved education during the academic years will be able to futures studies; therefore, it can be argued that one of the critical variables that can affect students' futures growth potential, is the quality of their teaching and learning methods. This study aim is to design teaching methods based on the development of futures studies in higher education which was conducted by using grounded theory by the qualitative research. In this study, 12 experts of curriculum areas and futures studies were interviewed. The full text of responses of interviewees was performed from a recorded version in the coding process, the given comments were divided by software MAXQDA 12 into separate concepts and then familiar concepts set in a separate category, and the component of teaching methods was identified as the major categories of research. In the final model, the barriers, strategies, and consequences had presented for compiling of the teaching methods based on the futures studies development separately and in the framework of the analysis models.